2017
DOI: 10.1002/2017jb014473
|View full text |Cite
|
Sign up to set email alerts
|

The induced earthquake sequence related to the St. Gallen deep geothermal project (Switzerland): Fault reactivation and fluid interactions imaged by microseismicity

Abstract: In July 2013, a sequence of more than 340 earthquakes was induced by reservoir stimulations and well‐control procedures following a gas kick at a deep geothermal drilling project close to the city of St. Gallen, Switzerland. The sequence culminated in an ML 3.5 earthquake, which was felt within 10–15 km from the epicenter. High‐quality earthquake locations and 3‐D reflection seismic data acquired in the St. Gallen project provide a unique data set, which allows high‐resolution studies of earthquake triggering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
124
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 53 publications
3
124
0
Order By: Relevance
“…A total volume of 175 m 3 of water was injected into the reservoir over a 2 hr period. The injection test induced a number of microseismic events (M L < 0.2), six of which were relocated by Diehl et al (2017) (Figure 1). The first events occurred roughly 80 min after the start of injection.…”
Section: Induced Seismicity During the Deep Geothermal Project In Stmentioning
confidence: 99%
See 1 more Smart Citation
“…A total volume of 175 m 3 of water was injected into the reservoir over a 2 hr period. The injection test induced a number of microseismic events (M L < 0.2), six of which were relocated by Diehl et al (2017) (Figure 1). The first events occurred roughly 80 min after the start of injection.…”
Section: Induced Seismicity During the Deep Geothermal Project In Stmentioning
confidence: 99%
“…While the acid stimulation only caused a few microseismic events, the well control injection led to hundreds of events over several days, including one M L 3.5 earthquake. The entire relocated seismic sequence (Diehl et al, 2017), from mid-July to the beginning of November, is shown on the map in Figure 1a. The seismicity aligns along a fault oriented SSW-NNE (strike 210 • ), which is consistent with the fault plane solution of the M L 3.5 main shock striking 209 • (Diehl et al, 2014).…”
Section: Induced Seismicity During the Deep Geothermal Project In Stmentioning
confidence: 99%
“…This reflects the rather opti-110 mistic view that the maximum possible induced earthquake in a reservoir with shear modulus depends on the injected volume, leading to a volume change and alterations in the deviatoric stresses, which are relaxed by the induced earthquake. However, a number of case studies point out that this threshold is exceeded, for example in Pohang, South Korea (Kang-Kun et al, 2019), St.Gallen, Switzerland (Diehl et al, 2017) and Western Canada (Atkinson et al, 2016). Thus, an alternative and more conservative view, shared by various authors (e.g., Mignan 115 et al (2015); Mignan et al (2017); Atkinson et al (2016); Van der Elst et al (2016); Gischig (2015)) suggests that the largest possible induced earthquake corresponds to the largest possible natural earthquake defined by the seismotectonic setting at a respective site.…”
Section: Mediation Of Induced Seismicitymentioning
confidence: 99%
“…To reduce the pressure buildup, drilling mud was pumped into the well, increasing significantly the micro‐earthquake activity and inducing an event of M L 2.1 on 20 July at 2:40 a.m. (local time). At 5:30 a.m., the largest event of the sequence occurred with a magnitude of M L 3.5 ( M W 3.3; Diehl et al, ), followed by hundreds of events in the next few months. The St. Gallen sequence ceased completely on 25 October 2013, following a production test (e.g., Moeck et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…On 19 July, methane gas was detected in the borehole. To reduce the pressure buildup, drilling mud was pumped into the well, increasing significantly the micro-earthquake Diehl et al, 2017), followed by hundreds of events in the next few months. The St. Gallen sequence ceased completely on 25 October 2013, following a production test (e.g., Moeck et al, 2015).…”
Section: Introductionmentioning
confidence: 99%